(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Objective: Aims at recognizing the haematological abnormalities in peripheral blood associated with HIV infection and to correlate the haematological abnormalities with CD4 cell count to highlight these manifestations with disease progression. Methodology: Observational cross sectional study. Setting: Department of Haematology, Armed Forces Institute of Pathology (AFIP), Dhaka cantonment. Patients: Two hundred four (204) HIV infected patients receiving antiretroviral therapy aged from three years to 65 years. There were 132 male and 72 female patients. Results: Anaemia was found in 103 (50.5%) cases. Leucopenia and thrombocytopenia were observed in ten (4.9%) and seven (3.4%) cases respectively. Lymphopenia was found in 12 (5.9%) cases. In 50 (24.5%) cases Erythrocyte Sedimentation Rate (ESR) was > 20 mm at the end of 1st hour. Flow cytometric analysis for CD4 cell count showed < 200 cells/cmm in 65 (31.8%) cases, in between 200 cells/cmm and 499 cells/cmm in 117 (57.4%) cases and > 500 cells/cmm in 22 (10.8%) cases. Conclusion: Haematological abnormalities are common in HIV infected patients and responsible for significant morbidity and mortality in these patients. These abnormalities are more frequent with disease progression. The present study revealed a significant increase in the number of anaemia, leucopenia, lymphopenia and thrombocytopenia with decreasing CD4 cell count. J Bangladesh Coll Phys Surg 2014; 32: 130-136